2002
DOI: 10.1007/s00024-002-8693-z
|View full text |Cite
|
Sign up to set email alerts
|

Lyapunov Exponents for 2-D Ray Tracing Without Interfaces

Abstract: The Lyapunov exponents quantify the exponential divergence of rays asymptotically, along infinitely long rays. The Lyapunov exponent for a finite 2-D ray and the average Lyapunov exponents for a set of finite 2-D rays and for a 2-D velocity model are introduced. The equations for the estimation of the average Lyapunov exponents in a given smooth 2-D velocity model without interfaces are proposed and illustrated by a numerical example. The equations allow the average exponential divergence of rays and exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…An attempt to quantify the exponential divergence of rays with respect to the complexity of the model and to formulate explicit criteria enabling the construction of models suitable for ray tracing was made by Klimeš [14]. In his paper, he observed that, for an isotropic medium and a model parametrization with bi/tricubic splines, the average Lyapunov exponent may be approximated by the square root of the Sobolev norm of order 2 (appendix A) of the corresponding velocity model [15,1]:…”
Section: Introductionmentioning
confidence: 99%
“…An attempt to quantify the exponential divergence of rays with respect to the complexity of the model and to formulate explicit criteria enabling the construction of models suitable for ray tracing was made by Klimeš [14]. In his paper, he observed that, for an isotropic medium and a model parametrization with bi/tricubic splines, the average Lyapunov exponent may be approximated by the square root of the Sobolev norm of order 2 (appendix A) of the corresponding velocity model [15,1]:…”
Section: Introductionmentioning
confidence: 99%